Mourning and Widowhood in Polish Traditional Culture - Rzepnikowska, Iwona (Literatura Ludowa. Journal of Folklore and Popular Culture, 2025)
This paper explores the themes of mourning and widowhood in Polish folk culture. Ethnographic sources and texts of verbal folklore are used as exemplification material. The analysis of mourning considers its duration and its correlation with the sex, age, family and social status of the deceased. It also examines mourning clothing, rules of behaviour in everyday and ritual life for the relatives of the deceased, the marking of the house of mourning, the notification of village inhabitants about the death and the vigil held at the body of the deceased. Meanwhile, the phenomenon of widowhood is considered in the context of the idea of oddity. On the one hand, this manifests itself in the negative valorisation of widowed individuals, especially as candidates for spouses, and on the other hand, in the desire and even the need to enter into another relationship. Symbolically, this can be understood as striving for parity, stability and wholeness. In practice, re-marriage had a more pragmatic dimension, dictated by purely economic considerations.